What can a jump tell us about elbow injuries in professional baseball pitchers? - Mayberry, J.; Mullen, S.; Murayama, S. (The American Journal of Sports Medicine, 2020)
Background: The incidence rate of elbow injuries has been rising in recent years among professional baseball pitchers. Determining valid screening procedures that allow practitioners to identify pitchers at an increased risk of such injuries is therefore of critical importance.